2015
DOI: 10.1186/s12912-015-0095-5
|View full text |Cite
|
Sign up to set email alerts
|

Professional practice models for nurses in low-income countries: an integrative review

Abstract: BackgroundAttention is turning to nurses, who form the greatest proportion of health personnel worldwide, to play a greater role in delivering health services amidst a severe human resources for health crisis and overwhelming disease burden in low-income countries. Nurse leaders in low-income countries must consider essential context for nurses to fulfill their professional obligation to deliver safe and reliable health services. Professional practice models (PPMs) have been proposed as a framework for strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…Participants were unsure about which interventions fell within and outside their scope. This appears consistent with findings discussed by Byrne ( 2015 ) in an integrative review, who found discordance between actual and expected nursing practice in terms of non-nursing roles being performed by nurses.…”
Section: Discussionsupporting
confidence: 91%
“…Participants were unsure about which interventions fell within and outside their scope. This appears consistent with findings discussed by Byrne ( 2015 ) in an integrative review, who found discordance between actual and expected nursing practice in terms of non-nursing roles being performed by nurses.…”
Section: Discussionsupporting
confidence: 91%
“…IENs' from high‐income countries are thought to have an advantage as they are educated and trained to work in similar healthcare environments. Conversely, IENs from low‐income countries, where the requirements to practise nursing may differ from high‐income countries (Ng'ang'a & Woods Byrne ), often arrive in the destination country unprepared to meet the standards set forth by regulatory bodies. In addition, differences in the way nursing is practised, that is duties, organization and efficiency of care, specialization (Primeau et al, ) can create additional practice gaps for IENs from low‐income countries.…”
Section: Introductionmentioning
confidence: 99%
“…An unclear clinical responsibility assigned to nurses in their healthcare domain is described as a reason for low legitimacy for policies facilitating nurse leadership in Jordan [ 30 ]. Enhancing the image of nursing sector is seen as crucial step towards creating an enabling environment for national structures and processes that facilitate nurses’ leadership [ 31 , 32 ]. The structural forces that shape the perception of nursing will be a major challenge in India.…”
Section: Discussionmentioning
confidence: 99%